Analysis Of Factors That Affect The Financial Disstress Of Life Insurance Companies Registered With The Financial Services Authority For The Period 2020 - 2022 - Mufid, Muhammad Farras (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
This study analyzes the variables that influence financial distress in life insurance companies. The population under study consists of life insurance companies registered with the OJK during the period of 2020-2022. The research sample comprises 37 companies with a total of 111 data observations that meet the purposive sampling criteria. The main findings indicate that profitability and capital have a negative impact on financial distress, while company size has a positive influence. Liquidity and governance do not show a significant effect on financial distress. The practical implications of these results can assist company management in decision-making to enhance financial performance.